Lyda Borelli’s Satanic Rhapsody: The Cinema and the Occult - Vacche, Angela (Cinémas, 2005)
AbstractDiscussing Nino Oxilia’s film Satanic Rhapsody (Rapsodia Satanica, 1915) starring Lyda Borelli, the author examines the influence of Bergsonism on the perception of cinema right before and during World War I. In particular, she points out the intersection between the film and, among other references, the tradition of the early Italian diva film, the plastic dynamism of Futurist painter Umberto Boccioni, the dance/performance art of Loïe Fuller, and the emerging figure of the New Woman.